WATER SOLUBLE NITROGENOUS COMPONENT FROM SQUILLA (ORATO SQUILLANEPA) - NAIR, A LEKSHMY; PRABHU, P V (Fishery Technology, 2017)
A water soluble hygroscopic powder has been isolated from squilla in good yield,ranging from 3.5 to 5.0 per cent of the fresh raw material, by a simple direct method. The process com:ists of homogenising squilla with an equal quantity of water, removal of chitinous matter from the slurry by filtration, heating the filtrate at 0.7 kgfsq.cm steam pressure for 15-20 minutes, removal of the precipitated protein by filtration and concentration and final drying in vacuum of the filtered cooled liquor. The pale brown powder so obtained consists mainly of peptones and proteoses and has been found to be comparable to BDH peptone for growth of bacteria, ability to serve as source for tryptophan for indole production and to provide substrate for the production of hydrogen Â·sulphide. Comparative studies have been made on similar water solublefractions from two species of prawns, namely, Metapenaeus affinis and Parapenaeopsis stylifera.